Xanthomonas wilt of banana - Blomme, Guy; Kearsley, Elizabeth; Ocimati, Walter (Burleigh Dodds Science Publishing Limited, 2023)
Xanthomonas wilt (BXW) is a major banana disease affecting small-holder farms in East and Central Africa. While BXW management practices have been introduced across extensive regions, achieving high levels of disease control and/or eradication has proven difficult. Resurgence of BXW in managed sites and the transmission to new regions are ongoing problems. In this chapter we present an overview of the disease epidemiology followed by the state-of-the-art of BXW control and prevention measures. We address management practices that have shown variable adoption successes, and present innovations recently introduced (including Single Diseased Stem Removal and improved tool sterilization options) or underway (including the development of resistant cultivars, and risk mitigation through early warning systems). Next, we discuss lessons learned from problems that have arisen during phases of implementation of management, the constraints that local farmers face and the shift towards sustainable management through integrated participatory extension services.